Khivan Historical Manuscripts of the 19th-the Early 20thCentury (Journal of Oriental Studies, 2018)
This article is based on the research some of Khiva historical works. The surviving Khivan narrativesources due to their content and diversity of facts have a special place among manuscripts of the CentralAsian region. In the works of Khiva historiographers are contained comprehensive data on the historyof the nomads, including Kazakhs that inhabited the territory of the Khivan khanate and its neighboringcountries. The Khivan historical manuscripts contain data specifying the tribal structure of Kazakhs of theKhivan Khanate as well as their settlements.The article is written in framework of realization of projectNo.AP05132796 of the Ministry of Education and Science of the Republic of Kazakhstan.